Hidden topological constellations and polyvalent charges in chiral nematic droplets - Gregor Posnjak (Nature Portfolio, 2017)
Once a purely mathematical discipline, topology has become an essential tool to investigate physical phenomena such as topological states in liquid crystals. Posnjaket al. observe the existence of 3D point defects of higher than unit topological charge in thermally quenched chiral nematic droplets.